Mixed circumferential hemorrhoidal prolapse. Combined treatment with mechanical stapler and laser coagulation (Revista Argentina de Cirugía, 2026)
Management of circumferential hemorrhoidal prolapse represents a challenge for surgeons. There arecurrently many alternatives to conventional procedures.; however, none of these techniques considertreatment of external disease. Even procedures associated with less postoperative pain as stapled hemorrhoidectomy or Doppler-guided hemorrhoidal artery ligation do not involve treatment of the external component.The aim of this publication is to present the technique detailed to treat patients with mixed hemorrhoidal prolapse, combining stapled hemorrhoidopexy with laser coagulation of external hemorrhoids.The results have been previously documented in a total of 25 patients, with 4% of complications. We conclude that the procedure is an option to consider in patients with circumferential hemorrhoidal prolapse with external component.
Keywords: hemorrhoids; hemorrhoidal prolapse; hemorrhoidopexy; laser photocoagulation of hemorrhoids